2018
DOI: 10.1128/iai.00166-18
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antibodies to VAR2CSA and Merozoite Antigens with Pregnancy Outcomes in Women Living in Yaoundé, Cameroon

Abstract: infections are serious in pregnant women, because VAR2CSA allows parasitized erythrocytes to sequester in the placenta, causing placental malaria (PM). In areas of endemicity, women have substantial malarial immunity prior to pregnancy, including antibodies to merozoite antigens, but produce antibodies to VAR2CSA only during pregnancy. The current study sought to determine the importance of antibodies to VAR2CSA and merozoite antigens in pregnant women in Yaoundé, Cameroon, where malaria transmission was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In fact, among the 104 PM-women at delivery only 31.7% and 30.8% had Ab to FV2 and DBL5 respectively, and only 12.5% of paucigravidae and 48% of MG had Ab to FV2 (Table 2). Although pre-IPT Ab prevalence in Etoudi is unknown, Ab prevalence to FV2 in PM-women living in Yaoundé prior to implementation was 24.3% in pauci-and 40.1% in MG [20]. Thus, with decreased transmission and extended use of IPT, today fewer women have Ab to FV2 during their first two pregnancies, but Ab prevalence is similar in MG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, among the 104 PM-women at delivery only 31.7% and 30.8% had Ab to FV2 and DBL5 respectively, and only 12.5% of paucigravidae and 48% of MG had Ab to FV2 (Table 2). Although pre-IPT Ab prevalence in Etoudi is unknown, Ab prevalence to FV2 in PM-women living in Yaoundé prior to implementation was 24.3% in pauci-and 40.1% in MG [20]. Thus, with decreased transmission and extended use of IPT, today fewer women have Ab to FV2 during their first two pregnancies, but Ab prevalence is similar in MG.…”
Section: Discussionmentioning
confidence: 95%
“…Within a given pattern, some variation is also observed; for example, in the equatorial pattern where this study was carried out, the transmission increases from the center urban to rural areas. Available data on Ab response to VAR2CSA in Cameroonian women exist only for central urban (low malaria transmission) [20,21] or rural area (high malaria transmission) [14,15,22,23], although these areas are usually separated by a peri-urban or sub-urban area where malaria transmission is intermediate or relatively low. In addition, most of previous studies on Ab response to VAR2CSA in Cameroon were carried out before the IPTp-SP implementation.…”
Section: Introductionmentioning
confidence: 99%
“…We found that positive antibody responses to pregnancy-specific antigens were associated with increased odds of peripheral infection in some studies, with varying degrees of significance [43,55,57,61]. At delivery, antibody responders (IgG) to the pRBC surface [35,53,61], to full-length VAR2CSA (FV2) [52,60], and to the vaccine candidate ID1-ID2a, which includes interdomain region 1, DBL2X, and interdomain region 2a, had increased odds of placental infection compared to non-responders [42,52] (Fig. 2a).…”
Section: Discussionmentioning
confidence: 99%
“…2a). Antibody responders to FV2, and VAR2CSA domains, with the exception of DBL4, had increased odds of placental infection compared to nonresponders [42,52,59,60,63] (Fig. 2a).…”
Section: Placental Infectionmentioning
confidence: 98%
See 1 more Smart Citation